2011
DOI: 10.1051/0004-6361/201117369
|View full text |Cite
|
Sign up to set email alerts
|

The complex behaviour of the microquasar GRS 1915+105 in theρclass observed withBeppoSAX

Abstract: Context. BeppoSAX observed GRS 1915+105 on October 2000 with a long pointing lasting about ten days. During this observation, the source was mainly in the ρ class characterized by bursts with a recurrence time of between 40 and 100 s. Aims. We identify five segments in the burst structure and accumulate the average spectra of these segments during each satellite orbit. We present a detailed spectral analysis aimed at determining variations that occur during the burst and understanding the physical process that… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
25
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 51 publications
7
25
0
Order By: Relevance
“…The idea that the QPO originates from the corona is also consistent with the fact that the QPO absolute amplitude is low at the pulse phase (Fig. 1) where the corona flux is at its minimum (Mineo et al 2012(Mineo et al , 2017, and with the result that both the QPO absolute amplitude and the corona flux at phase below ∼ 0.85 are coincidentally higher in the ρ2 class than in the ρ1 class ( Fig. 1; Fig.…”
Section: Qpo's Originsupporting
confidence: 78%
“…The idea that the QPO originates from the corona is also consistent with the fact that the QPO absolute amplitude is low at the pulse phase (Fig. 1) where the corona flux is at its minimum (Mineo et al 2012(Mineo et al , 2017, and with the result that both the QPO absolute amplitude and the corona flux at phase below ∼ 0.85 are coincidentally higher in the ρ2 class than in the ρ1 class ( Fig. 1; Fig.…”
Section: Qpo's Originsupporting
confidence: 78%
“…The energy spectra at the peak flux level and persistent flux level have been modelled with the disc blackbody (with and without zero-torque conditions) and powerlaw (with and without cut-off)/low temperature Comptonization (Yadav et al 1999;Nobili et al 2000;Trudolyubov 2001;Klein-Wolt et al 2002;Lee et al 2002;Fuchs et al 2003;Rodriguez et al 2008Rodriguez et al , 2004Martocchia et al 2006;Middleton et al 2006;Ueda et al 2009) or thermal Comptonization of disc blackbody photons along with the presence of a strong nonthermal component/powerlaw tail using RXTE/PCA, RXTE/HEXTE (Pahari & Pal 2010;Done et al 2004;Naik et al 2002b) simultaneously with OSSE/CGRO observations (Zdziarski et al 2001;Rau & Greiner 2003), SUZAKU observations , BeppoSAX observations (Mineo et al 2012) and INTEGRAL observations (Rodriguez et al 2008). Sobolewska & Zyśki (2003) observe that although HS state spectra are dominated by soft thermal emission, it is complex in nature and can not be described by a standard thermal disc.…”
Section: Introductionmentioning
confidence: 99%
“…Neilsen et al (2012) showed that about a third of all RXTE observations of GRS 1915+105 in the ρ-state show a single peak, 40% show a double peak and the rest show some intermediate shape. The oscillations in fitting parameters are similar to Neilsen et al (2011) and Mineo et al (2012) if we use the same models. The shapes, however, depend of the exact model used.…”
Section: The Continuummentioning
confidence: 68%
“…This suggested that the central region of the disk evaporates or becomes radiatively inefficient during the instability before refilling on a viscous timescale. This picture appeared to be supported by the spectral modeling of the different states (Belloni et al 1997(Belloni et al , 2000Mineo et al 2012). Uncertainties in disk atmosphere models (e.g., the density or the fraction of power dissipated in a corona) can, however, be important and may affect these inferred radius estimates significantly (e.g., Merloni et al 2000;Miller et al 2009).…”
Section: Introductionmentioning
confidence: 77%